A system of functional-differential equations associated with the optimal detection problem for jump-times of a Poisson process. (1998) - Donchev, Doncho S.
Abstract : The value function in the optimal detection problem for jump-times of a Poisson process satisfies a special system of functional-differential equations. In this paper, we investigate the system and prove the existence and uniqueness of its solution.